Pengaruh Pemanfaatan Teknologi Informasi, Kompetensi SDM dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan - Aried Sumekar; Ratna Dina Marviana; Listya Devi Junaidi (Owner : Riset dan Jurnal Akuntansi, 2025)
In Indonesia, a regulation has been established that requires small businesses to prepare financial statements or maintain proper accounting records, namely Minister of Cooperatives and Small and Medium Enterprises Regulation No. 2 of 2024 concerning Cooperative Accounting Policy. However, despite the enactment of this regulation, in reality, many MSME players still prepare financial statements that do not comply with standards, and some do not prepare financial statements at all. The purpose of this study is to identify the factors influencing the quality of financial statements in SMEs in the city of Medan. The research method chosen is a mixed-methods approach. The population in this study consists of SMEs registered with the Cooperative and SME Agency of the City of Medan. The sample was reduced using purposive sampling with selected criteria, resulting in a total of 113 samples. Data will be analyzed using path analysis (Smart PLS). The results of the analysis indicate that the three independent variables—information technology utilization, human resource competence, and internal control systems—have a positive and significant impact on the quality of SME financial statements. Among these three variables, the internal control system has the most dominant influence, with an effect size of 61.5%. This indicates that the better the implementation of internal control systems, the higher the quality of financial reports produced by SMEs. This finding has practical implications for SME development, particularly in strengthening internal control aspects and improving the utilization of information technology and human resource competencies to support the accountability and transparency of financial reports.